Cubic perturbed centrifugally stabilized excited state in orthorhombic manganites - Dutta, Joy; Adhikari, Satrajit; Kovaleva, N. N. (The Journal of chemical physics, 2019)
A model Hamiltonian for centrifugally stabilized electronic-vibrational motion of a cubic perturbed upper “Mexican hat” potential surface for a Mn3+ ion in an octahedral symmetry is formulated, and its eigenspectrum is explored. Theoretically calculated eigenvalues for cubic perturbed ground and excited electronic states are employed to interpret the origin of higher energy narrow side bands (satellite transitions) appearing in the dielectric function spectra of the LaMnO3 complex, which exhibit anomalous temperature dependence in the vicinity of the Néel temperature, TN ≃ 140 K [N. N. Kovaleva et al., J. Exp. Theor. Phys. 122, 890 (2016)].